MYC alterations in multiple myeloma: Genetic insights and prognostic impact - Sara Cristóbal-Vargas; Myriam Cuadrado; Norma C Gutiérrez (Neoplasia: An International Journal for Oncology Research)
Multiple myeloma (MM) is a hematologic malignancy with high genetic complexity. The genetic alterations that drive MM have classically been classified as primary abnormalities, including IGH translocations and hyperdiploidy, and secondary abnormalities, mainly composed of 1q gains, 17p deletions and MYC rearrangements. Dysregulation of the MYC oncogene has been proposed as a key factor in disease progression from monoclonal gammopathy of undetermined significance (MGUS), smoldering MM and overt MM. MYC, a multifunctional transcription factor, is frequently activated in MM through various mechanisms, including translocations, amplifications, and overexpression, thereby contributing to the growth and survival of malignant plasma cells. The role of MYC abnormalities in the prognosis of MM remains controversial and continues to be overlooked in current prognostic indices for MM. The different methodologies used to detect MYC lesions may hinder the interpretation of the apparently contradictory results between studies analyzing the impact of these alterations on the survival of MM patients. On the other hand, the mouse models that best mimic the characteristics of human MM are those driven by MYC.In this review, we provide an overview of the MYC alterations described in MM, indicating the methodologies used to detect them and discussing their influence on patient prognosis. We also summarize the main characteristics of the genetically engineered mouse models driven by MYC. Finally, we assess the therapeutic potential of MYC inhibition in MM and the strategies currently approved for clinic use.